Internalization of Consumed TiO2 Nanoparticles by a Model Invertebrate Organism. (14th May 2012) - Novak, Sara; Drobne, Damjana; Valant, Janez; Pelicon, Primož
Abstract : There is little in vivo data concerning the fate of ingested TiO2 nanoparticles (nano-TiO2 ). We report here experiments aimed at assessing if ingested nano-TiO2 accumulates in the digestive gland epithelium or are internalized elsewhere in the body of the terrestrial isopod crustaceans. The animals (Porcellio scaber, Isopoda, Crustacea) fed for 3, 7, or 14 days on food dosed with 100 or 1000 μg nano-TiO2 showed no evidence of internalization of Ti measured by microparticle-induced X-ray emission method. The effect of ingested nanoparticles was measured by conventional toxicity measures such as feeding rate, weight change, and mortality and did not indicate any toxicity. However, cell membrane of digestive glands, measured with a modified method for assessing cell membrane stability, was affected already after 3 days of exposure to 1000 μg nano-TiO2 per gram dry weight of food indicating cytotoxic potential of ingested nanoparticles. Our results confirmed hypothesis on low toxic potential and no internalization of consumed TiO2 nanoparticles by a model invertebrate organism. However, cytological marker unequivocally indicated adverse effect of ingested nano-TiO2 . We conclude that the isopod model system could be used for studying the fate and effect of ingested nanoparticles.